Does RNA editing compensate for Alu invasion of the primate genome?. (31st October 2014) - Levanon, Erez Y.; Eisenberg, Eli
<x xml:space="preserve">Abstract</x> One of the distinctive features of the primate genome is the Alu element, a repetitive short interspersed element, over a million highly similar copies of which account for >10% of the genome. A direct consequence of this feature is that primates' transcriptome is highly enriched in long stable dsRNA structures, the preferred target of adenosine deaminases acting on RNAs (ADARs), which are the enzymes catalyzing A‐to‐I RNA editing. Indeed, A‐to‐I editing by ADARs is extremely abundant in primates: over a hundred million editing sites exist in their genomes. However, there are few essential editing sites conserved across mammals that have maintained their editing level despite the radical change in ADAR target landscape. Here, we review and discuss the cost of having an unusual amount of dsRNA and editing in the transcriptome, as well as the opportunities it presents, which might have contributed to the accelerated evolution of the primates.